Human genome/exome sequencing – the bioethical aspect - Kochański, Andrzej (Studia Ecologiae et Bioethicae, 2014)
In recent years we have observed a technological revolution in genetics. For years molecular diagnostics in genetic disorders were limited to a single gene or to a group of genes. The technological breakdown in molecular genetics relies on the change of perspective from the analysis of a single gene to the whole genome sequencing (WGS) or whole-exome sequencing (WES). The exome is defined as a coding part of the genome consisting of the coding parts (exons) of all genes. Thus, at present geneticists have access to the whole genome instead of separate/selected genes. Clinical genetics in the era of genomic sequencing has to cope with new challenges concerning the confidentiality of genetic data, genetic discrimination, genetic and clinical determinism, or incidental findings detected in genome analysis. This short review attempts to demonstrate the ethical challenges faced in the era of genome sequencing.